Corrosion Behaviour of Additively Manufactured High Entropy Alloys - MATTHEW RITCHIE (2024)
Additive manufacturing (AM) is a modern manufacturing technique that facilitates the production of components layer by layer from CAD files, with more recent developments in the field leading to the ability to create these components from metal. Laser powder bed fusion (LPBF) is one of the many techniques used to manufacture metallic components and has drawn significant attention for its ability to create parts with high degrees of complexity, exceptional strength-to-weight ratios and internal structures. However, parts produced by AM are documented to suffer from build defects such as porosity, which can negatively affect not only its mechanical properties but its corrosion resistance,particularly its resistance to pitting corrosion. Whilst the mechanical properties of components produced through metal AM have been well documented since the technology’s inception, there are significant knowledge gaps in understanding the corrosion behaviour of metals produced in this way.This thesis aims to expand upon the current understanding of this manufacturing method with a particular focus on its corrosion resistance. High Entropy Alloys (HEAs) are a class of advanced materials that differ from conventional alloys in composition. Traditional alloys usually consist of one or two principal elements with smaller amounts of additional elements to impart specific properties. In contrast, HEAs are characterised by the presence of multiple principal elements in roughly equal proportions. HEAs' complex and disordered structure can result in unique mechanical, thermal, and magnetic properties. HEAs have shown promise in exhibiting high strength, hardness, and corrosion resistance, making them attractive for various engineering applications. Studies of HEAs have been increasing over recent years; however, significant knowledge gaps are still associated with this classification of materials, especially concerning their corrosion resistance. This lack of knowledge is intensified when discussing the properties of these alloys when manufactured by AM methods.LPBF was used to produce parts in 316L with process induced porosity by manipulating the process parameters to investigate the effect density has on the corrosion resistance of AM parts. The corrosion resistance of these parts were compared to their wrought counterpart using potentiodynamic polarisation. It was observed that increasing the porosity in the AM parts resulted in poorer corrosion resistance, both by weaker performance across key metrics and a greater degree of unreliability. It was also found that the AM parts proved to have a greater corrosion resistance than the wrought material. However, the decreased consistency in this resistance is often cited as a barrier these components must overcome to supplace conventionally manufactured components.316L was also produced through induction casting as well as a schedule more representative of industry that consisted of a solution anneal at 1080 °C followed by water quenching followed by a cold rolling reduction by 70 %, and a final anneal at 900 °C. The microstructures and corrosion resistance of these were investigated using SEM-EDS, XRD and potentiodynamic polarisation, and whilst the corrosion resistance of the cold rolled sample had increased, it was less than expected due to the formation of detrimental chromium carbides.A Swansea University developed AlCrFeMnNi HEA was put through the same 3 manufacturing processes to investigate their effect on the microstructure and corrosion resistance. It was found that, unlike 316L, the HEA suffered less from pitting corrosion and more from a generalised corrosion attack. Very similar corrosion results were seen across the manufacturing methods; however, the cast sample was observed to have the most consistent display of corrosion resistance.Based on the pitting resistance equivalent number, which relates the amount of Cr and Mo by wt.% in a stainless steel to its corrosion resistance, it was theorised that the addition of Mo to this HEA could also increase its corrosion resistance. The results were inconclusive; however, better corrosion resistance was seen in the AM sample of the HEA with the addition than in the AM sample without.